PERAN PASRAMAN KILAT DALAM MENINGKATKAN SRADHA DAN BHAKTI SISWA DI SMK NEGERI 1 GIANYAR (PERSPEKTIF ANTROPOLOGI AGAMA HINDU) - sari, wayan siska; Wira Diputra, Gede Bagus; Supadmini, Ni Kadek; Mardika, I Made Nasib (Guna Widya: Jurnal Pendidikan Hindu, 2026)
People who wish to deepen their knowledge of Hinduism generally do so through education at the Pasraman (traditional shrine). Pasramans serve as places of development, expected to shape better individuals and benefit their families and communities. In Bali, the Pasraman plays a crucial role in shaping the next generation of qualified Hindus. Currently, children and adolescents are busy with school activities, so much of their time is spent on formal education. To strengthen their devotion and devotion, the Bali Provincial Government initiated activities that can be integrated into the school environment, namely Pasraman Kilat. This study aims to measure and assess the role of Pasraman Kilat in increasing the sradha and bhakti of students at SMK Negeri 1 Gianyar. The research method used is a qualitative method through observation and literature study. The research results show that the Pasraman Kilat activity was able to increase students' understanding of Hindu teachings in greater depth. This understanding contributes to increasing students' devotion and devotion to Ida Sang Hyang Widhi Wasa. Pasraman Kilat activities include practical lessons in Mejejaitan, Balinese dance, and tabuh.